Pertanggungjawaban Bank Terhadap Nasabah yang Menjadi Korban Kejahatan yang Dilakukan Oleh Oknum Internal Bank - I Putu Wiradharma Putra Yudha; Johannes Ibrahim Kosasih; Desak Gde Dwi Arini (Jurnal Konstruksi Hukum, 2021)
Banks are the only financial institutions that are trusted by the people who play a role in the economy, so that in their activities there are elements of stakeholders who commit acts against the law in the banking world. This study aims to analyze crimes committed by internal bank employees and reveal legal liability to the bank if there are crimes committed by internal elements or bank employees. This study uses normative legal research with a statutory approach and a conceptual approach. The data used are primary and secondary data obtained through recording and documentation techniques, then the data processed and analyzed will be processed and analyzed using a systematic legal material processing method. The results of the study stated that in banking there are two types of violations, namely banking crimes and crimes in banking. In relation to crimes in the banking sector, Law no. 7/1992 as amended by Law No.10/1998 on banking. Accountability cannot be borne by the bank as a corporation, but this burden is imposed or carried out by way of the debtor to individuals who commit crimes in the banking sector.